STOX2 but not STOX1 is differentially expressed in decidua from preeclamptic women: Data from the Second Nord-Trøndelag Health Study - Fenstad, M.; Johnson, M.; Løset, M.; Mundal, S.; Roten, L.; Eide, I.; Bjørge, L.; Sande, R.; Johansson, A.; Dyer, T.; Forsmo, S.; Blangero, J.; et al. (2010)
Variation in the Storkhead box-1 (STOX1) gene has previously been associated with pre-eclampsia. In this study, we assess candidate single nucleotide polymorphisms (SNPs) in STOX1 in an independent population cohort of pre-eclamptic (n = 1.139) and non-pre-eclamptic (n = 2.269) women (the HUNT2 study). We also compare gene expression levels of STOX1 and its paralogue, Storkhead box-2 (STOX2) in decidual tissue from pregnancies complicated by pre-eclampsia and/or fetal growth restriction (FGR) (n = 40) to expression levels in decidual tissue from uncomplicated pregnancies (n = 59). We cannot confirm association of the candidate SNPs to pre-eclampsia (P > 0.05). For STOX1, no differential gene expression was observed in any of the case groups, whereas STOX2 showed significantly lower expression in deciduas from pregnancies complicated by both pre-eclampsia and FGR as compared with controls (P = 0.01). We further report a strong correlation between transcriptional alterations reported previously in choriocarcinoma cells over expressing STOX1A and alterations observed in decidual tissue of pre-eclamptic women with FGR. © The Author 2010. Published by Oxford University Press on behalf of the European Society of Human Reproduction and Embryology.